Biopesticides and Refugia Implementation Increasing the Population and Diversity of Natural Enemies in Rice Fields based on Ecology - Muhammad Izza Kurniawan; Ramadhani Mahendra Kusuma; Sri Wiyatiningsih (The University of Lampung, 2025)
The diversity of natural enemies of insects is influenced by the availability of microhabitats and food sources, which can be increased through the use of refugia. Intensive use of pesticides in conventional agricultural systems has resulted in a decline in the diversity of natural enemies that play an important role in biological control of pests. This study aims to identify the types, roles, and populations of natural enemies of pests and determine the level of natural enemy diversity including the species diversity index, species evenness, species richness, and dominance in rice fields using integrated and conventional farming systems. Data collection methods were carried out through a combination of direct observation, insect nets, yellow traps, light traps, and identification of insect morphospecies using a digital microscope and supporting literature. The identification results showed 7 orders and 21 genera of natural enemies with a total of 4,679 individuals in integrated fields and 2,792 individuals in conventional fields. The species diversity index (H’=2.11), evenness (E’=0.69), species richness (R’=2.37), and dominance (C’=0.18) indicated that the integrated system was more supportive of biodiversity. Ecological engineering through refugia has been shown to increase the population diversity of natural enemies, thereby strengthening biological control in rice ecosystems.